Sudden Infant Death Syndrome From Pathophysiological Prospects - Sawaguchi, Toshiko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
Sudden infant death syndrome (SIDS) is characterised by the sudden death of an infant that is not predicted by prior medical history and it is still responsible for a large percentage of infant mortalities. The exact causes have long remained unknown, though some risk factors such as including exposure to tobacco smoke, no breast feeding, and prone sleeping position, have been identified. However an analysis linking neurophysiological and neuropathological aspects in a prospective study of SIDS suggests that one of the causes of SIDS is arousal deficiency. This unique book provides the latest, comprehensive information on SIDS research from epidemiology to physiology.
1. Sudden infant death syndrome and the pedunculpontine tegmental nucleus -- 2. Developmental alteration of hypocretins (orexins) in the brainstem in the sudden infant death syndrome -- 3. Sudden infant death syndrome from epidemiology to pathophysiology: Exploring the connections -- 4. Sleep deprivation in infants, children and adolescents -- 5. Sleep disturbance in children resulting from noises exposure -- 6. Sudden infant death syndrome from the perspective of arousal deficiency -- 7. Cerebral blood oxygenation changes over the occipital and frontal cortexes during sucking in infants: an optical topographic study -- 8. Mismatch negativity in healthy neonates and premature babies.
Keywords: Medicine; Forensic Medicine; Neurology; Pediatrics; Medicine & Public Health; Pediatrics; Neurology; Forensic Medicine